Interrelationship among Quality of Work-Life, Islamic Work Ethics, and Employee Performance: Employee Engagement as Mediator (Equilibrium: Jurnal Ekonomi Syariah, 2022)
This study aims to examine the effect of quality of work-life and Islamic work ethics on employee performance and the mediating role of employee engagement among quality of work-life, Islamic work ethics and employee performance. The paper explicitly highlighted the conduct and outcomes of the study. A quantitative survey approach was used to collect necessary data by applying the instruments adopted from previous studies. The reliability and validity of tools were above the standard. Out of 250 sets of questionnaires distributed to the employees working with Small and Medium Enterprises (SMEs) throughout Kudus region, Central Java, Indonesia, a sample size of 194 has been utilized for data analysis to test study hypothesis. The path analysis indicated that quality of work-life and Islamic work ethics contributed significantly to employee engagement, subsequently to employee performance. However, the quality of work-life had no significant direct effect on employee performance as such the relationship was fully mediated by employee engagement, whereas employee engagement partial mediated on Islamic work ethics and employee performance. Thus, spiritual adoption of work ethics seems a necessity for today’s business organization. Therefore, it is recommended to SMEs’ owners and practitioners that they could improve their business performance through improved quality of work-life, Islamic work ethics, and employee engagement.